Regulating mobile money to create an enabling business environment - Kausch, Bronwen Ashley (My University, 2013)
The technology to deliver mobile money services has been in place for over a decade, yet very few mobile money operations have reached scale. The purpose of the following research is to explore the possible reasons for this by analysing factors which impact the rollout and uptake of services. This is achieved through a case study of mobile money service offerings in the developing world in general and South Africa in particular. Findings of the research highlight the complexities of the challenge of reaching scale, particularly those relating to regulations, finding the appropriate business models and other socio-political factors. A further finding points to a possible lack of appropriate skills in the mobile money industry as a reason for services not reaching scale.
Keywords: Mobile commerce; South Africa